Brigatinib treated ALK positive lung squamous cell carcinoma after failed chemotherapy: A case report. Issue 23 (13th October 2021) - Li, Shuluan; Zhang, Pei; Wang, Tianyu; Wang, Jie; Duan, Jianchun
Abstract: The definitive efficacy of anaplastic lymphoma kinase (ALK) inhibitors in ALK positive lung squamous cell carcinoma (sqCC) patients remain unclear. Here, we report a case in which brigatinib had a therapeutic effect on ALK‐positive lung squamous cell carcinoma. The patient in this report was diagnosed with ALK‐positive lung squamous cell carcinoma with brain metastases, and received brigatinib after failure of first‐line chemotherapy. Response duration was approximately 11 months, with tolerable side effects. In conclusion, a good clinical effect was achieved in a patient with ALK positive lung squamous cell carcinoma who received treatment with an ALK inhibitor. Abstract : Our case was first report to determine the excellent antitumor effect of Brigatinib on ALK positive lung SqCC. PFS was more than 11 months, and the side effects were tolerable.